2017
DOI: 10.2217/epi-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of SLFN11 is a Marker of Poor Prognosis and Cisplatin Resistance in Colorectal Cancer

Abstract: SLFN11 is frequently methylated in human CRC, and the expression of SLFN11 is regulated by promoter region methylation. Methylation of SLFN11 reduced the sensitivity of CRC cells to cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…Consistent with earlier analyses of the NCI-60 cell lines [19,20] and with growing evidence for the role of epigenetic mechanisms in SLFN11 inactivation [21,69,81], we found that increased methylation of the SLFN11 promoter was negatively correlated with SLFN11 expression and increased resistance of SCLC lines to DNA-damaging agents (Supplementary Figure 3). Association of SCLC promoter methylation with gene expression and with drug sensitivity are in agreement with the findings of He et al [82], who showed that increased methylation of the SLFN11 promoter in colorectal cancer cell lines and primary tumors led to downregulation of SLFN11 expression, increased tumor resistance to cisplatin, and decreased the 5-year overall patient survival and 5-year progression-free survival.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with earlier analyses of the NCI-60 cell lines [19,20] and with growing evidence for the role of epigenetic mechanisms in SLFN11 inactivation [21,69,81], we found that increased methylation of the SLFN11 promoter was negatively correlated with SLFN11 expression and increased resistance of SCLC lines to DNA-damaging agents (Supplementary Figure 3). Association of SCLC promoter methylation with gene expression and with drug sensitivity are in agreement with the findings of He et al [82], who showed that increased methylation of the SLFN11 promoter in colorectal cancer cell lines and primary tumors led to downregulation of SLFN11 expression, increased tumor resistance to cisplatin, and decreased the 5-year overall patient survival and 5-year progression-free survival.…”
Section: Discussionsupporting
confidence: 91%
“…Although we found no signi cant correlation between SLFN11 expression and other clinicopathological variables (Table 3), SLFN11 expression levels tended to be lower in older patients. A previous report suggested that high levels of methylation of SLFN11 were signi cantly associated with older age (32). Bioinformatics analysis using CellMinerCDB (https://discover.nci.nih.gov/cellminercdb/) demonstrated a strong inverse correlation between SLFN11 methylation in promoter regions and its mRNA expression level (r = -0.750, p = 0.00013; Figure S2) (30,31).…”
Section: Slfn11 Expression and Agementioning
confidence: 74%
“…This may also be relevant to ICF syndrome patients with HELLS mutations, given that hypomethylation of repeat sequences is observed at a subset of chromosomes and the most frequently observed mutations in ICF syndrome are within DNMT3b (Hansen et al, 1999;Jin et al, 2008). In addition, HELLS has been associated with hypomethylation of specific repeat elements in some colorectal tumours and loss of DNA methylation has been linked to metastasis (Samuelsson et al, 2016;He et al, 2017). However, DNA methylation does not occur in budding yeast and consequently it seems likely to be the function at heterochromatic regions or DNA repair that is conserved in the yeast homolog, Irc5.…”
Section: Discussionmentioning
confidence: 99%